Dark disciple - Golden, Christie (Del Rey, 2015)
The Jedi Council pairs brash Jedi Knight Quinlan Vos with infamous one-time Sith acolyte Asajj Ventress to target and kill the man responsible for so many war atrocities, Count Dooku himself.